Space Information Technology in the Arctic Policy of the European Union - A. P. Kovalev; I. M. Levkin; K. A. Naumenko (Управленческое консультирование)
The article describes the status of the most important part of the Arctic information policy of the European Union — space of information security. The data on the number and types of space systems of Earth remote sensing used by the European Union over the past fifteen years and analyzes the role of space information technology in achieving the main goals of the Arctic policy of the European Union.